2018
DOI: 10.1590/s0004-2803.201800000-09
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors Increase the Overall Risk of Developing Bacterial Infections in Patients With Cirrhosis

Abstract: -Background -Acid suppression has been associated with adverse events; such as, enteric infections. Proton pump inhibitors (PPI) are frequently prescribed in patients with cirrhosis, but is unclear if PPI are associated with the development of bacterial infections in these patients. Objective -To assess the impact of PPI intake on the development of bacterial, viral and fungal infections in patients with cirrhosis. Methods -An observational, retrospective, historic cohort study. The exposed cohort included pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…Because patients with hepatitis and cirrhosis often have high stress ulcers of the digestive tract, such as coagulation dysfunction, PPIs are routinely used for gastric protection; however, there are no reports on the rational evaluation of their use in China. Some studies indicate that patients with liver cirrhosis are prone to bacterial infections 24,25 because of their impaired immune status, the increased use of invasive procedures, and alterations in the enteric flora. 26,27 For example, Hermos et al 10 showed that use of PPI would increase the risk of CAP by 1.80-fold when compared with non–PPI use in liver disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because patients with hepatitis and cirrhosis often have high stress ulcers of the digestive tract, such as coagulation dysfunction, PPIs are routinely used for gastric protection; however, there are no reports on the rational evaluation of their use in China. Some studies indicate that patients with liver cirrhosis are prone to bacterial infections 24,25 because of their impaired immune status, the increased use of invasive procedures, and alterations in the enteric flora. 26,27 For example, Hermos et al 10 showed that use of PPI would increase the risk of CAP by 1.80-fold when compared with non–PPI use in liver disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…After full-text reviews, 29 studies were selected for the final analysis. Thirteen articles reported the results of case-control studies [19][20][21][22][23][24][25][26][27][28][29][30][31] and 16 the results of cohort study [12,13,[32][33][34][35][36][37][38][39][40][41][42][43][44][45] Figure 1 summarizes the study selection process and Table 1 shows the characteristics of the studies involved. A total of 20,484 participants across the 29 studies were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 35 full-length articles were thoroughly reviewed, and 27 articles were further excluded as they did not report the outcome of interest. Finally, 3 cohort and 5 cross-sectional studies with a total of 40,295 participants met the eligibility criteria and were included in the metaanalysis [10][11][12][13][14][15][16][17]. Two of the 3 included cohort studies were published as conference abstracts [10,14].…”
Section: Resultsmentioning
confidence: 99%
“…The use of PPI may also lead to an increased risk of other types of organspecific bacterial infection. In fact, studies have suggested an increased risk of bacterial pneumonia among cirrhotic patients who use PPIs, although the results are inconsistent [10][11][12][13][14][15][16][17]. The current study aimed to further investigate this risk by identifying all available studies and summarizing their results together.…”
Section: Introductionmentioning
confidence: 99%